IDENTIFYING THE DIMENSIONS IMPACTING THE CURRENT TAX REGIME ON INDIAN MSMES: A LITERATURE REVIEW - Usha Devi; Rekha Rani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In India, MSMEs are vital to the economy, providing a substantial number of jobs and income. The growth and development of these enterprises are influenced by tax laws, economic elements, and other relevant factors. Changes in India’s income tax structure in recent years have impacted businesses, including MSMEs. To understand these effects, this review paper aims to compare the impact of different tax structures and economic elements on MSMEs. India’s economy has undergone significant changes, necessitating research to address the challenges faced by MSMEs. However, there is a lack of studies combining these factors in the context of MSMEs, highlighting the need for comparative analysis. The review comprehensively constructs a conceptual model based on a literature review to understand the relationship between MSME performance, growth, and the current tax regime.